2008
DOI: 10.4049/jimmunol.180.2.817
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Neutrophil-Derived Ectosomes Interfere with the Maturation of Monocyte-Derived Dendritic Cells

Abstract: Polymorphonuclear neutrophils (PMNs) are a key component of the innate immune system. Their activation leads to the release of potent antimicrobial agents through degranulation. Simultaneously, PMNs release cell surface-derived microvesicles, so-called ectosomes (PMN-Ect). PMN-Ect are rightside-out vesicles with a diameter of 50–200 nm. They expose phosphatidylserine in the outer leaflet of their membrane and down-modulate monocyte/macrophage-activation in vitro. In this study, we analyzed the effects of PMN-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 52 publications
(75 reference statements)
7
165
0
6
Order By: Relevance
“…Further, they demonstrated that PMN-derived EVs increased the secretion of the anti-inflammatory cytokine TGF-β1 from monocytes, whereas the stimulated release of IL-8, IL-10 and TNFα was decreased [40]. Secretion of TGF-β1 was induced also in monocyte-derived dendritic cells, where incubation with PMN-EVs interfered with the LPS-induced differentiation process indicated by a decrease of release of inflammatory cytokines, decrease of phagocytosis and T-cell stimulation [34]. The inhibitory effects were initiated by membrane components of PMN-EVs which led to the activation of the Mer tyrosine kinase pathway in monocytes, resulting eventually in inhibition of transcription factor NF-κB and downregulation of several pro-inflammatory genes [35].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, they demonstrated that PMN-derived EVs increased the secretion of the anti-inflammatory cytokine TGF-β1 from monocytes, whereas the stimulated release of IL-8, IL-10 and TNFα was decreased [40]. Secretion of TGF-β1 was induced also in monocyte-derived dendritic cells, where incubation with PMN-EVs interfered with the LPS-induced differentiation process indicated by a decrease of release of inflammatory cytokines, decrease of phagocytosis and T-cell stimulation [34]. The inhibitory effects were initiated by membrane components of PMN-EVs which led to the activation of the Mer tyrosine kinase pathway in monocytes, resulting eventually in inhibition of transcription factor NF-κB and downregulation of several pro-inflammatory genes [35].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 97%
“…Most of the data on PMN-derived EVs (called in these studies ectosomes) come from the laboratory of Dr. Schifferli [26,[34][35][36]39,40,45,[93][94][95][96]. They characterized the size and surface properties of EVs released upon fMLP-stimulation and came to the conclusion that both the in vitro and the in vivo generated EVs are right-side out [39,45].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 99%
“…Exosomes bear specific protein markers such as tetraspanins (CD63,CD9,CD81), HeatShock proteins (HSP 70) or the Transferin Receptor in the case of reticulocyte (TfR), that make the exosomes distincts from vesicles released upon plasma membrane shedding and called ectosomes [3]. These latter contain distinct markers such as glycophorin.…”
Section: A Biogenesis and Release Of Exosomes By Producer Cells: Fromentioning
confidence: 99%
“…PS present in the outer surface of ectosomes is found to be responsible for the immunomodulatory property of ectosomes (Gasser and Schifferli, 2004), and a specific receptor protein tyrosine kinase (i.e., Mer receptor tyrosine kinase) is involved in the intracellular signaling process (Scott et al, 2001). PMN-derived ectosomes also have an inhibitory effect on immature DCs (Eken et al, 2008;Gasser and Schifferli, 2004). Thus, when immature DCs are cultured with LPS in the presence of PMN-derived ectosomes, expression levels of the cytokines and costimulatory and adhesion ligands required for T cell activation are significantly reduced, compromising T cell activation.…”
Section: Biological Roles Of Ectosomesmentioning
confidence: 99%